Design, Synthesis, Hypoglycemic Activity and Molecular Docking Studies of 3-substituted-5- [(furan-2-yl)-methylene]-thiazolidine-2,4-dione Derivatives - Kumar, Karumanchi Srikanth; Rao, Atmakuri Lakshmana; Reddy, Dachuru Rama Sekhara (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: From the wide range of previous literature studies indicated that thiazolidinedione’s reacts with substituted benzaldehydes undergoes knoevenagel condensation gives respective arylidene derivatives. In our attempt all the titled compounds were designed and developed by replacement of substituted benzaldehydes with furan- 2-aldehyde, so that furan moiety was introduced in the molecule. Materials and Methods: 5-[(furan-2-yl)-methylene]-thiazolidine-2,4-dione was prepared via knoevenagel condensation by the reaction of thiazolidine-2,4-dione and furfural. Further it was coupled with various alkyl/ aryl halides in alcoholic potassium hydroxide to produce various derivatives 2a-2j. The titled compounds furthermore prepared by microwave assisted synthesis technique. Synthesized compounds were analysed by physical and spectral characterization methods. Developed furan bearing thiazolidine-2,4-diones were evaluated for in-vivo hypoglycemic property. Molecular docking analysis was carried out to observe the binding interaction of designed ligands at PPARγ target receptor protein. Results and Conclusion: Microwave irradiation technique produced high yield at less reaction time in comparison with traditional conventional method. In-vivo hypoglycemic activity evaluation revealed that, electron releasing groups (-OH and –OCH3) containing compounds 2d and 2g found to possess significant activity in acute study as well as in chronic study. Even the molecular docking studies at PPARγ receptor protein (PDB ID- 2PRG), electron releasing groups containing compounds 2d and 2g exhibit significant binding affinity having high binding energy of -9.02 kcal/mol and -8.61 kcal/mol when compared with standard ligand rosiglitazone.
Keywords: Thiazolidinedione derivatives; Synthesis; Hypoglycemic Activity; Molecular; Docking; PDB ID-2PRG